Study on the effect of Fermentation and Resource Utilization of Municipal Sludge. Issue 5 (April 2019) - Yang, Yang; Li, Junwei; Yan, Hongyu; Wang, Shuai
Abstract: In this study, a large number of field experiments were carried out to study the aerobic fermentation of dewatered activated sludge by using the dewatered sludge of Harbin Municipal Sewage Treatment Plant as raw material and using a horizontal rotary aerobic sludge fermentation device. The paper also studied the effect of fermented activated sludge as o rganic fertilizer in the field. The results showed that the sludge fermentation temperature continued to rise from 50 t o 55 °C, and the highest temperature was 58 °C. The water content of sludge decreases gradually with the extension of fermentation time. After 17 days of fermentation, the water content of sludge decreases from 60% to 40%. The change of ammonia nitrogen shows that it first increases and then decreases. Although the content of nitrate nitrogen increases and decreases, the value of start and end of fermentation has not changed much. Total nitrogen content showed a downward trend. Cellulose can be degraded rapidly in the early stage of sludge fermentation, but slowly in the later stage. Aerobic fermentation is an effective way for sludge resource utilization.